Pengembangan Media Pembelajaran Audio Visual Berbasis Powtoon Pada Pembelajaran IPA Materi Sifat Dan Perubahan Wujud Benda Kelas IV Sekolah Dasar - Yuni Ellyas Asmara; Wahyudi; Sutrisno Sahari (Jayapangus Press, 2023)
This research is the result of the researcher's observations, with the finding that learning activities in elementary schools have not used concrete learning media to convey material, especially related to material about the nature and changes in the shape of objects. The media used is still minimal and lacks innovation, because the ability of teachers is still lacking in developing learning media, the teacher's lack of time to make media, and the lack of ideas in utilizing learning media to support the learning process of students. This study aims to determine the validity, practicality, and effectiveness of Powtoon-based audio-visual learning media developed for science learning in grade IV. This research is a type of R&D (Research and Development) research with adaptation to the ADDIE development model (analizys, design, development, implementation, and evaluation). Subjects in the study included teachers and fourth grade students at SDN Mrican 1 Kediri. The results of this study indicate that (1) the validity of the media obtained an average result for the media 96.25%, while for the material obtained 90%, it was declared valid for learning media, (2) the practicality of the media obtained the average teacher response questionnaire results. reaches 96%, it is declared practical as a learning medium without revision. (3) the effectiveness of the media obtained an average evaluation result with 21 students reaching 90%, so it can be declared effective to be used in the process of learning activities. From the results of this study, through a learning model that uses Powtoon-based audio-visual related to natural science material about the nature and changes in the shape of objects, it shows good results and is accepted by students. Then the results of research related to Powtoon-based audio-visual media can make students understand more about material properties and changes in object shape and can increase student enthusiasm in class.